2007
DOI: 10.1103/physreve.76.031121
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dissipation effect in Brownian relaxation

Abstract: In an ensemble of non-interacting Brownian particles, a finite systematic average velocity may temporarily develop, even if it is zero initially. The effect originates from a small nonlinear correction to the dissipative force, causing the equation for the first moment of velocity to couple to moments of higher order. The effect may be relevant when a complex system dissociates in a viscous medium with conservation of momentum.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 27 publications
0
35
1
Order By: Relevance
“…It has been shown that the stationary probability distribution function (PDF) is independent of magnitudes of additive and multiplicative noises and of the relaxation time of colored noise [20][21][22]29], although the response to applied input depends on noise parameters [29]. This is in contrast with previous studies [30][31][32] which show that the stationary PDF of the Langevin model for the harmonic potential is Gaussian or non-Gaussian, depending on magnitudes of additive and multiplicative noises.…”
Section: Introductioncontrasting
confidence: 54%
See 4 more Smart Citations
“…It has been shown that the stationary probability distribution function (PDF) is independent of magnitudes of additive and multiplicative noises and of the relaxation time of colored noise [20][21][22]29], although the response to applied input depends on noise parameters [29]. This is in contrast with previous studies [30][31][32] which show that the stationary PDF of the Langevin model for the harmonic potential is Gaussian or non-Gaussian, depending on magnitudes of additive and multiplicative noises.…”
Section: Introductioncontrasting
confidence: 54%
“…We consider a system of a Brownian particle coupled to a bath consisting of N -body uncoupled oscillators, which is described by the generalized CL model [20][21][22]29],…”
Section: A Non-markovian Langevin Equationmentioning
confidence: 99%
See 3 more Smart Citations